2018
DOI: 10.1051/cocv/2017001
|View full text |Cite
|
Sign up to set email alerts
|

On the semi-global stabilizability of the Korteweg-de Vries Equationviamodel predictive control

Abstract: Stabilization of the nonlinear Korteweg-de Vries (KdV) equation on a bounded interval by model predictive control (MPC) is investigated. This MPC strategy does not need any terminal cost or terminal constraint to guarantee the stability. The semi-global stabilizability is the key condition. Based on this condition, the suboptimality and exponential stability of the model predictive control are investigated. Finally, numerical experiment is presented which validates the theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…In the light of our recent investigations on analysis of RHC for infinite-dimensional systems in [3,6,4], the novelty of the present paper lies in the following facts: 1. Here we deal with time-varying systems.…”
Section: Algorithm 1 Receding Horizon Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of our recent investigations on analysis of RHC for infinite-dimensional systems in [3,6,4], the novelty of the present paper lies in the following facts: 1. Here we deal with time-varying systems.…”
Section: Algorithm 1 Receding Horizon Algorithmmentioning
confidence: 99%
“…The last term in (3) is the L 1 -penalization of the switching constraint u i (t)u j (t) = 0 for i = j and t > 0. See e.g., [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to Algorithm 1, for every j ∈ {r, • • • , r + Θ} we have one of the cases α k+j = α BB1 k+j or α k+j = α BB2 k+j . Further, using (9), the fact that A is self-adjoint, and the spectral property (8), we have for every k ≥ 1 and q = 0, 1, 2, that…”
Section: General Casementioning
confidence: 99%
“…By putting m = r n u η , (44) holds. Moreover, the equivalence of ( 44) with ( 45) is justified due the fact that, similarly to (9) for G k , it can easily be shown that…”
Section: General Casementioning
confidence: 99%
See 1 more Smart Citation